EXPERIMENTAL ESTIMATION OF DOUBLE AMPLITUDE OF THE OSCIRAL PROCESS OF TORQUE CHANGE ON A BIT - Moisyshyn, V. M.; Ivasiutyn, A. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article aims to establish, based on the results of bench-top experimental studies, the influence of external independent factors, which include axial static load, rotational speed n, stiffness C, and damping coefficient β of the drilling tool, on the double amplitude of the dynamic component of the torque on the bit. Bench studies were made using method ofrational design experiments, so that a combination of studies of independent officials occurs only once. A planned factorial experiment was carried out on sandstone blocks of the Vorotyshchenska Svita, folded between two layers with a hardness of 1440 and 2050 MPa. Constant factors during the drilling period in the bench washes were the type and diameter of three roller bits and the amount of washing liquid (water). The results of the investigations were based on empirical models of multiple nonlinear correlations between the variable amplitude of the colliding process, changing the overturning moment on the bit, and changing agents for inlays. Sand hardness is 1440 and 2050 MPa. An analysis of the influx of changeable officials was carried out to determine the main patterns of change in partial deposits and the type of rock hardness.